2023
DOI: 10.1177/0193841x231182749
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Economic Corridor and Tourism on Local Community's Quality of Life under One Belt One Road Context

Shiying Wang,
Jaffar Abbas,
Khalid Ibrahim Al-Sulati
et al.

Abstract: Economic corridors unlock new economic opportunities and tourism development in the region to achieve sustainable development goals. Green economic growth is conducive to environmental sustainability. Economic mega-projects of CPEC promote tourism that leads to communities’ well-being and better quality of life. Modern infrastructure development contributes significantly to economic growth and tourism activities. This study’s objectives emphasize exploring tourism and sustainable development pursuits under OBO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 119 publications
0
9
0
1
Order By: Relevance
“…Previous studies have indicated that employees' resistance to change and their career sustainability are both affected by social and organizational factors [24,25], and leadership, as an important organizational factor, is considered useful in dealing with both. For instance, Lundy et al [26] found that in the Canadian public service sector, "project leadership" can effectively reduce employees' resistance to change through proper training.…”
Section: Paradoxical Leadership Resistance To Digital Technology and ...mentioning
confidence: 99%
“…Previous studies have indicated that employees' resistance to change and their career sustainability are both affected by social and organizational factors [24,25], and leadership, as an important organizational factor, is considered useful in dealing with both. For instance, Lundy et al [26] found that in the Canadian public service sector, "project leadership" can effectively reduce employees' resistance to change through proper training.…”
Section: Paradoxical Leadership Resistance To Digital Technology and ...mentioning
confidence: 99%
“…The varying interpretations emphasize the multifaceted nature of debt's influence on firm performance, ranging from increased costs of capital due to higher debts to positive signals perceived by shareholders. Moreover, the Miller & Modigliani theory underscores the role of tax shields in enhancing profitability [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…But our study includes 5 years of latest data and ROA, ROE, and EPS as profitability indicators. Our research increases the number of firms to assess the impacts that capital structure has on a firm's financial performance [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sewage-treatment technologies have also received considerable attention from researchers. With the help of Internet and new technology like big data, the bio-ecological combination treatment technology could meet the differentiated needs of rural domestic sewage treatment in China and had great potential for development and utilization [ 1 , 32 , 33 ].…”
Section: Literature Reviewmentioning
confidence: 99%